2014
DOI: 10.1007/s11255-014-0893-9
|View full text |Cite
|
Sign up to set email alerts
|

Do the different types of renal surgery impact the quality of life in the postoperative period?

Abstract: Total nephrectomy was a negative predictor of overall global health status. There is a demand for a reasonable follow-up program with an individual control interval according to the risk of recurrence and the possibility of treatment as well as the patient's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 10 publications
2
17
0
1
Order By: Relevance
“…Nevertheless, our findings suggest that PN is superior, to some extent, to RN with regard to QoL following treatment of tumors stage T1 [ 14 , 16 ]. Similar results were found in studies that included patients with more advanced tumors, by Poulakis et al [ 23 ] and Azawi et al [ 8 ]. Even though Poulakis et al did not find major differences in QoL between RN and PN overall, the authors found a significant difference in several QoL domains between RN and elective PN [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, our findings suggest that PN is superior, to some extent, to RN with regard to QoL following treatment of tumors stage T1 [ 14 , 16 ]. Similar results were found in studies that included patients with more advanced tumors, by Poulakis et al [ 23 ] and Azawi et al [ 8 ]. Even though Poulakis et al did not find major differences in QoL between RN and PN overall, the authors found a significant difference in several QoL domains between RN and elective PN [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, oncological outcomes, as well as potential differences between QoL and complication rate after different NSS procedures, are important considerations. In addition, surgical complications present a risk of prolonging recovery [ 7 ] and decreasing QoL after NSS [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To minimize this risk, patients were given sufficient time to think about their answers and if they were not willing to give a response by phone, they received the questionnaire by mail and were offered a follow-up telephone consultation. Our response rate, using this approach, was 75.5% which is in accordance with other survey studies and resulted in a reliable selection to perform our analyses [38][39][40][41]. Second, the GFI is a self-reported questionnaire.…”
Section: Discussionsupporting
confidence: 72%
“…To date, only four studies have attempted QoL comparisons in patients undergoing PN vs RN [21][22][23][24]. Results generally found that patients undergoing PN scored higher on physical functioning than patients undergoing RN.…”
Section: Discussionmentioning
confidence: 99%